Clinic friendly estimation of muscle composition: Preoperative linear segmentation shows overall survival correlated with muscle mass in patients with nonmetastatic renal cell carcinoma - Schmeusser, Benjamin N.; Midenberg, Eric; Palacios, Arnold R.; Vettikattu, Nikhil; Patil, Dattatraya H.; Medline, Alexandra; Higgins, Michelle; Armas-Phan, Manuel; Nabavizadeh, Reza; Joshi, Shreyas S.; Narayan, Vikram M.; Psutka, Sarah P.; et al. (Frontiers in Oncology, 2022)
Purpose: Sarcopenia is associated with decreased survival and increased complications in patients with renal cell carcinoma. Readily identifying patients with low muscle composition that may experience worse outcomes or would benefit from preoperative intervention is of clinical interest. Traditional body composition analysis methods are resource intensive; therefore, linear segmentation with routine imaging has been proposed as a clinically practical alternative. This study assesses linear segmentation’s prognostic utility in nonmetastatic renal cell carcinoma. Materials and Methods: A single institution retrospective analysis of patients that underwent nephrectomy for nonmetastatic renal cell carcinoma from 2005-2021 was conducted. Linear segmentation of the bilateral psoas/paraspinal muscles was completed on preoperative imaging. Total muscle area and total muscle index associations with overall survival were determined by multivariable analysis. Results: 532 (388 clear cell) patients were analyzed, with median (IQR) total muscle index of 28.6cm2/m2 (25.8-32.5) for women and 33.3cm2/m2 (29.1-36.9) for men. Low total muscle index was associated with decreased survival (HR=1.96, 95% CI 1.32-2.90, p<0.001). Graded increases in total muscle index were associated with better survival (HR=0.95, 95% CI 0.92-0.99, p=0.006). Conclusions: Linear segmentation, a clinically feasible technique to assess muscle composition, has prognostic utility in patients with localized renal cell carcinoma, allowing for incorporation of muscle composition analysis into clinical decision-making. Muscle mass determined by linear segmentation was associated with overall survival in patients with nonmetastatic renal cell carcinoma.